Regulatory effect of arginine metabolism enzymes on ethyl carbamate formation during the fermentation of Chinese yellow rice wine - FANG Ruosi; DONG Yachen; XU Tengyang; FAN Linlin; CHEN Qihe (浙江大学学报. 农业与生命科学版)
Ethyl carbamate (EC) is a potential carcinogenic compound in most of fermented products. It widely exists in the fermented foods, especially alcohol beverages, such as grape wine, Japanese sake and Chinese yellow rice wine, etc. Thus, the search for effective methods to reduce EC level in final products must be carried on and considered. It has been reported that the optimal production methods for grape wine and high quality strains were capable of reducing the level of EC in grape wine product. Arginine is one of the major amino acids found in grape wine, which can be decomposed to the precursors of EC by yeast and malolactic fermentation bacteria. The degradation of arginine by lactic acid bacteria via the arginine deiminase (ADI) pathway has been reported. It involves three enzymes: ADI, ornithine transcarbamoylase (OTC) and carbamate kinase. The degradation of arginine metabolism produced ammonia, adenosine triphosphate, ornithine, carbamyl phosphate and some citrullines. Studies have shown that citrulline is a typical indicator of EC level in grape wine, and a correlation between citrulline production and ethyl carbamate formation by Lactobacillus hilgardii isolated from grape wines is reported. As generally acknowledged, urea is considered as the major precursor of EC production in grape wine fermentation which can be degraded by urease.In this study, different disposals were taken during the brewing process. The control group was designed without adding any inhibitor, whereas in the experimental groups, 0.001, 0.01, 0.2 mol/L L-ornithine hydrochlorides were added, and 150, 750 U ureases per 1.5 kg solid at the eighth day were added as inhibitors, respectively.As a result, both the inhibitors acted well. The highest level of EC content in control group was 169 mg/L, while in the experimental groups with 0.01mol/L L-ornithine hydrochloride and 150 U urease, the EC contents were 78.81 and 58.55 mg/L, respectively. Urea and citrulline both were the major substrates of EC production.Combining the data of EC formation and OTC activity, it can be concluded that the increase in intracellular OTC activity has an inhibition effect on EC formation in the processing of Chinese yellow rice wine. Nevertheless, the detailed regulatory mechanism still is under illustration for the processing in the future study.